Urinary stress incontinence in women who practice physical activities: prevalence and associated factors - Ana Paula da Silva Farias Tietz; Natália Cristina de Oliveira Vargas e Silva (O Mundo da Saúde, 2018)
Urinary incontinence is defined as any involuntary loss of urine, with stress urinary incontinence (SUI) being the most common type. SUI negatively impacts the quality of life of women in their social interactions and health perception, even leading them to abandon their practice of physical activity. The prevalence of SUI among women who practice recreational physical activities varies between 25% and 49.3%, however, literature is still scarce in studies about this issue. Therefore, the aim of this study was to identify the prevalence of SUI and associated factors among women who practice recreational physical activities. Data were obtained through the application of a questionnaire given to the attendants of all the State Family Social Centers (SFSC) in the city of Manaus-AM (Brazil). The sample included women aged between 18 and 55 years old. The sample was composed of 215 women, with mean age of 41.0 ± 9.3 years. The prevalence of SUI symptoms was 9.3%. Most participants (85.1%) had one or more children, and caesarean section (52.6%) predominated. 78.1% of them reported not having undergone any gynecological surgery. Most participants attended recreational physical activities more than 3x/week (57.2%), for longer than 6 months (54.9%). The prevalence of SUI among participants of this study was low in relation to previous studies and was associated with the number of vaginal deliveries.